FEATURES OF DEVELOPMENT OF ACCOUNTING POLICY OF TRADE ENTERPRISES (INNOVATIVE ECONOMY, 2021)
Shmyhel O.Ye. FEATURES OF DEVELOPMENT OF ACCOUNTING POLICY OF TRADE ENTERPRISESPurpose. The aim of the article is the development of separate elements and stages of accounting policy of trade enterprises taking into account their adaptation to the international standards of accounting and financial reporting.Methodology of research. The theoretical and informational basis of the study were the works of leading economists in the field of accounting, as well as national and international standards of accounting and financial reporting. In the process of research general and special methods were used, in particular: the method of classification allowed to differentiate the main components of accounting of trade enterprises, and the method of description gave them a detailed description; the monographic method is used in the study of literature sources on the creation of the main aspects of the accounting policy of commercial enterprises; the system and analytical method is applied at processing of the received information.Findings. Approaches to determining the peculiarities of trade enterprises and accounting are considered. Identification characteristics and values for drawing up the accounting policy of trade enterprises are substantiated. The main problems that arise when compiling the accounting policy of commercial enterprises are identified. The place of accounting policy in the accounting and analytical system of trade enterprises is determined. Options for organizing the accounting policy of commercial enterprises in compliance with international standards of accounting and financial reporting are considered.Originality. The peculiarities of the organization of the accounting policy of trade enterprises with observance of the international standards of accounting and financial reporting are substantiated.Practical value. The obtained theoretical and applied recommendations can be used to improve existing approaches to the accounting policy of commercial enterprises.Key words: trade enterprise, accounting policy, stages of development, elements of accounting, development technology, reporting, accounting standards.
Keywords: Key words; trade enterprise; accounting policy; stages of development; elements of accounting; development technology; reporting; accounting standards.